2020
DOI: 10.1016/j.jpeds.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Family Rooms in Neonatal Intensive Care Units and Neonatal Outcomes: An International Survey and Linked Cohort Study

Abstract: Objectives: To evaluate the proportion of neonatal intensive care units with facilities supporting parental presence in their infants' rooms throughout the 24-hour day (i.e., infant-parent rooms) in highincome countries and to analyze the association of this with outcomes of extremely preterm infants. Study design: In this survey and linked cohort study, we analyzed unit design and facilities for parents in 10 neonatal networks of 11 countries. We compared the composite outcome of mortality or major morbidity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 19 publications
(28 reference statements)
0
35
0
Order By: Relevance
“…A recent study reported that singlefamily room care lowered the risk for BPD (adjusted odds ratio 0.72, 95% confidence interval 0.61-0.86). 34 Our results can be a potential explanation for the mechanism behind this association, because single-family room care is related to more frequent and longer SSC. 35 Our study has limitations.…”
Section: Discussionmentioning
confidence: 62%
“…A recent study reported that singlefamily room care lowered the risk for BPD (adjusted odds ratio 0.72, 95% confidence interval 0.61-0.86). 34 Our results can be a potential explanation for the mechanism behind this association, because single-family room care is related to more frequent and longer SSC. 35 Our study has limitations.…”
Section: Discussionmentioning
confidence: 62%
“…It is shown that parents’ involvement in infants’ care in hospital enhance long-term cognitive and neurobehavioral development of preterm infants [ 9 14 ]. Moreover, increased parental presence and availability of family rooms shorten infants’ hospital stays [ 15 , 16 ]. Skin-to-Skin Contact (SSC) is an effective way to increase closeness.…”
Section: Introductionmentioning
confidence: 99%
“…This alleviates parental anxiety and distress at separation, and allows parents to play more of a role in their infant's care, potentially including extended periods of 'Kangaroo care. Unfortunately, most neonatal units in high-income countries currently lack facilities to support parents' presence 24 hours per day (Lehtonen et al, 2020).…”
Section: Preterm Birth Brain Development and Early Carementioning
confidence: 99%
“…Facilitating parental presence in the NICU may therefore promote better long-term outcomes for preterm babies. Rates of infant mortality, serious medical complications and poorer cognitive functioning are lower in infants cared for in NICUs with access to single family rooms, in which parents can stay with their child 24 hours per day (Lehtonen et al, 2020;Vohr et al, 2017). This alleviates parental anxiety and distress at separation, and allows parents to play more of a role in their infant's care, potentially including extended periods of 'Kangaroo care.…”
Section: Preterm Birth Brain Development and Early Carementioning
confidence: 99%